A Survey of Low Duty Cycle MAC Protocols in Wireless Sensor Networks - Ahmad, Mohd Riduan (INTECH, 2010)
This chapter examines various important low duty cycle MAC protocols and the two most important MAC protocols designed specifically for cooperative Multiple-Input Multiple- Output (MIMO) transmission. In most cases, the low duty cycle MAC protocols trade off latency for energy efficient operation. Also, we can observe later that asynchronous MAC protocols are more scalable than synchronous MAC protocols.